Book Review – 2024 - Honglan Wang; Paula Marcelle; Amelia Taylor; Metin Kocaturk; Michael Thomas; Şeyda Kır (Journal of Interactive Media in Education)
The following publication contains book reviews of these titles: • Olivier, J., Oojorah A., Udhin, W. (eds) (2022) Perspectives on teacher education in the digital age. Singapore: Springer Nature. 241 pages. ISBN 978-981-19-4225-9 • Isaacs, S., Mishra, S. (2022). Smart education strategies for teaching and learning: Critical analytical framework and case studies. Moscow: UNESCO Institute for Information Technologies in Education. 158 pages. ISBN: 978-5-906399-13-7. Open Access: http://hdl.handle.net/11599/4464 • Popenici, S. (2022). Artificial intelligence and learning futures: Critical narratives of technology and imagination in higher education. Routledge. 228 pages. ISBN: 978-1-032-20852-7 • Moore, S. L., Tillberg-Webb, H. K. (2023). Ethics and Educational Technology: Reflection, Interrogation, and Design as a Framework for Practice. Routledge. 328 pages. ISBN: 978-0-415-89508-8 • Conrad, D. (ed) (2023) Research, writing, and creative process in open and distance education: Tales from the field. Cambridge, UK: Open Book Publishers. 239 pages, ISBN Paperback: 978-1-80511-094-1